The extirpation of species outside protected areas. Issue 1 (21st September 2018) - Boakes, Elizabeth H.; Fuller, Richard A.; McGowan, Philip J.K.
Abstract: Protected areas (PAs) are fundamental to conservation efforts but they are only part of a successful conservation strategy. We examine biodiversity outside PAs in Sundaland, one of the world's most biologically degraded regions. Using the avian order Galliformes as a case study, we identify species that have not been sighted outside PAs within the last 20 years on each individual landmass (i.e., Malay Peninsula, Borneo, Sumatra, Java, and Bali). We estimate these species' extirpation dates outside PAs using optimal linear estimation and species' sighting records. We conclude there have been up to 13 extirpations of Galliformes from outside PAs in Sundaland. Three Sundaic endemics now occur only inside PAs. Sumatra has suffered the highest proportion of extirpations (50% of its galliform species). Effective management of Sundaland's PAs is thus critical to species' persistence and the conservation strategy for species outside PAs must be improved.